The Role of P‐Wave Variables in Enhancing Prediction of New‐Onset Atrial Fibrillation in Patients With Acute Myocardial Infarction - Na Yang; Xiaoyan Li; Bo Wu; Longhao Dai; Shaobin Yang; Qinning Zhang; Shaobin Jia (Annals of Noninvasive Electrocardiology)
ABSTRACT Background After acute myocardial infarction (AMI), it is common to observe new‐onset atrial fibrillation (NOAF), which is often related to a negative prognosis. Some P‐wave variables (P‐wave duration [PWD], P‐wave amplitude, and interatrial block [IAB]), reflecting the process of electrical and structural remodeling, could predict the risk of atrial fibrillation (AF). This study aimed to assess the predictive value of P‐wave variables for post‐AMI NOAF. Methods We retrospectively analyzed 1581 AMI patients with no prior AF, using follow‐up data from January 2023 to January 2024. P‐wave variables were measured, and patients were grouped based on in‐hospital NOAF occurrence. Results Overall, 164 (10.3%) of the 1581 patients had NOAF. The age (61.08 ± 12.02 vs. 67.91 ± 11.60, p < 0.001), left atrial size (36.31 ± 3.94 vs. 39.12 ± 5.51, p < 0.001), Brain Natriuretic Peptide (1588.45 ± 3346.18 vs. 3864.39 ± 6251.92, p < 0.001), P‐wave variables (PWD: 102.78 ± 12.56 vs. 117.88 ± 18.81, p < 0.001; P‐wave amplitude: 0.12 ± 0.04 vs. 0.13 ± 0.04, p = 0.041; interatrial block: 89.6% vs. 10.3%, p < 0.001), congestive heart failure (4.7% vs. 23.2%, p < 0.001), and Killip > 1 (25.3% vs. 55.5%, p < 0.001) showed significant differences between the non‐AF and NOAF groups. P‐wave variables were significantly associated with an increased risk of NOAF in multivariable regression analysis. Conclusions The addition of P‐wave variables to AF risk factors from literature and guidelines significantly improved NOAF risk discrimination. P‐wave variables were strongly associated with NOAF after AMI. Adding these variables enhanced the predictive performance for post‐AMI NOAF.